Ex ante and ex post approaches in transfer pricing documentation: A review of PMK 172 of 2023 and examination practices by the tax officers - Irawan, Ferry; Gumilang, Galih (Educoretax, 2025)
This article examines the mismatch between ex ante and ex post approaches in the preparation of transfer pricing documentation in Indonesia. While Ministry of Finance Regulation No. 172/2023 clearly mandates the use of the ex ante approach—where documentation is prepared based on information available at or before the time of the transaction—tax auditors often apply the ex post approach during audits by assessing actual outcomes. This inconsistency creates legal uncertainty and may discourage voluntary compliance among taxpayers. Using a normative-qualitative method and literature review, this study explores the issue from the perspective of regulations, audit practices, and international guidelines. A case study is included to illustrate how ex post adjustments can lead to disputes despite compliance with regulatory expectations. The article calls for harmonization between policy and enforcement practices to foster a more consistent, fair, and predictable tax system in Indonesia.